Mathematics in Good Will Hunting I: the mathematicians in Good Will Hunting - Korándi, József; Pluhár, Gabriella (Teaching Mathematics and Computer Science, 2012)
This is the first part of a three paper long series exploring the role of mathematicians and of the mathematical content occurring in popular media. In particular, we analyze the movie Good Will Hunting. In the present paper we investigate stereotypes about mathematicians living in the society and appearing in Good Will Hunting.